Radical health : unwellness, care, and Latinx expressive culture - Minich, Julie Avril, 1977- (Duke University Press, 2023)
"In Radical Health, Julie Avril Minich explores Latinx expressive culture to see how Latinx cultural workers connect compulsory health to structural racism, and how their work reimagines health along collective and political lines. Bringing a disability justice approach to questions of physical and mental health, Minich shows how artists, writers, and others make visible the social context of individual healthcare decisions, especially factors beyond individual control such as access to nutritious food, medical care and information, clean air and water, and cultural representations portraying one's life as valuable and worth living. From the poetry of Rafael Campo to the music of Hurray for the Riff Raff, the novels and short stories of Junot Diaz, the online visual and writerly activism of Virgie Tovar, and beyond, Minich shows how cultural works depict people who are labeled as unhealthy and reject the stigma of unhealth. In so doing, she argues, Latinx cultural workers push against respectability politics and "health normativity" to provide an interrogation of health as an ideological construct"--